1987
DOI: 10.1002/1097-0142(19870101)59:1<6::aid-cncr2820590106>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma of the lung. A progress report of 15 years' experience

Abstract: To assess the results of therapeutic advances in the treatment of small cell carcinoma of the lung (SCCL) achieved during the past 15-year period at a single large institution, 508 patients treated between 1968 and 1982 were divided into two groups: 157 patients (66 in the category of limited-stage disease and 91 in the extensive-stage disease category) treated with low-dose small-volume radiotherapy (RT) (time dose fractionation [TDF] 49-66) and with cyclophosphamide alone or a COPP program during the first p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Its features are: rapid progression, short doubling time, high growth fraction, and sensitivity to multiple chemotherapeutic agents and radiation therapy. Short-term survival seems to have improved since the introduction of chemotherapy in the 1970s [107,108,112]. In Mersey and Yorkshire, England, UK, the population-based 2-year survival rate improved from 2% in the 1970s to 8% in the 1980s and in the southeastern part of The Netherlands the population-based relative 1-year survival rate improved from 15% in the 1970s to 35% in the 1980s, but there was no further improvement in the 1990s and 2-year survival did not exceed 8% [106,113].…”
Section: Variations Between Histological Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its features are: rapid progression, short doubling time, high growth fraction, and sensitivity to multiple chemotherapeutic agents and radiation therapy. Short-term survival seems to have improved since the introduction of chemotherapy in the 1970s [107,108,112]. In Mersey and Yorkshire, England, UK, the population-based 2-year survival rate improved from 2% in the 1970s to 8% in the 1980s and in the southeastern part of The Netherlands the population-based relative 1-year survival rate improved from 15% in the 1970s to 35% in the 1980s, but there was no further improvement in the 1990s and 2-year survival did not exceed 8% [106,113].…”
Section: Variations Between Histological Subtypesmentioning
confidence: 99%
“…Furthermore, results of chemotherapy have reached a plateau and further improvement seems impossible with the currently available tools [106 -108,152]. The response rates and survival rates after combination chemotherapy with irradiation were moderately higher than after combination chemotherapy alone [112,[153][154][155][156].…”
Section: Small-cell Lung Cancermentioning
confidence: 99%
“…Previous studies have shown some progress in survival since the introduction of chemotherapy: 1-year relative survival rates improved from 18% in the 1970s to more than 30% in the 1990s for patients up to 70 years and from 9% to almost 20% for the elderly. 4,7,[43][44][45] We have shown that survival for the group of patients with SCLC as a whole has not further improved since the early 1990s, except for age group 45 to 59 years since the mid-2000s. However, when stratifying according to stage, 1-year relative survival for both patients with LD and ED has improved, as was also found in an American study.…”
Section: Trends In Prognosismentioning
confidence: 94%
“…1ā€“4 Despite a favorable initial response to chemotherapy, the prognosis for these patients remains poor, with a median survival time of 8 to 9 months. Treatment results in the 1990s have plateaued with no major advances in therapy as compared with the 1970s.…”
mentioning
confidence: 99%